Line-of-sight guidance law for path following of amphibious hovercrafts with big and time-varying sideslip compensation - Wang, Yuanhui; Tong, Haiyan; Fu, Mingyu (Ocean engineering, 2019)
We present a novel nonlinear adaptive path following controller that compensates for drift forces though time-varying sideslip for amphibious hovercrafts. The sideslip arises and changes with time during path following when the hovercraft is subject to drift forces caused by ocean disturbances or control forces. The time-varying sideslip of hovercraft is estimated online and independent of the tracking error by a bounded-gain-forgetting (BGF) adaptive estimator. Then, a line-of-sight (LOS) guidance law based on BGF is designed to follow the desired path accurately in the presence of ocean disturbances, in which the parameter estimation and the tracking errors are both proven to be bounded. Furthermore, the closed-loop cascade BGF-LOS guidance system, which is composed of tracking subsystem and sideslip parameter estimation subsystem, is proven to be input-to-state stable (ISS) according to the stability theory of cascaded system. The proposed guidance law is intended for maneuvering of an amphibious hovercraft in the horizontal-plane to follow a predefined parametrized curve without time constraints. The theoretical results are supported by two cases studies of an amphibious hovercraft.